Effect of age on the treatment duration and proposed “impacted incisor severity score” of impacted maxillary incisor: A retrospective study - Umer Mukhtar; Manoj kumar Jaiswal; Rigzen Tamchos; Ashima Goyal; Satinder Pal Singh; Aditi Kapur (Journal of Oral Biology and Craniofacial Research)
Background: Absence of anterior maxillary teeth has a significantly impact on esthetics, speech, mastication, and psychosocial well-being in young patients. Materials and methods: A retrospective study was conducted from January 2012 to January 2022, the data include children (8–15 years) with maxillary impacted incisors. After initial screening of the digital records, 75 cases with 80 impacted maxillary central incisors were recruited; 9 cases were excluded due to incomplete records. Results: 75 patients were found to have impacted incisors with a prevalence of 0.21 %. Patients were then divided into group 1 (<11years) and group 2 (11–15years) with a mean age of 9.51 ± 1.2 and 13.31 ± 1.74, respectively. Patients who reported at 11–15 years of age were significantly more as compared to <11years (p = 0.014). Among the various etiological factors, physical obstruction or inadequate space was found to be most common. Among dilacerated teeth, 75 % had a history of trauma, and only 35 % of normal impacted central incisors had a history of trauma (p = 0.00139). The mean duration of treatment time was found to be 16.77 ± 8.83months and 21.75 ± 6.08months for impacted incisors with normal morphology and with dilaceration, respectively and the difference was statistically significant (p = 0.042). Conclusions: Considering the age of the patient, it does not show significant effect on the duration of treatment, but a change in root morphology like dilaceration, significantly increases the duration of treatment. In addition, the proposed objective scoring system “Impacted incisor severity score” could help the clinicians to assess the difficulty and duration of treatment of impacted incisors.